2013
DOI: 10.1524/zpch.2013.0401
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pathways of Photoaddition Reactions by Artificial Force Induced Reaction Method: A Case Study on the Paternò–Büchi Reaction

Abstract: The present study demonstrates a priori prediction of the mechanism of Paternò-Büchi (PB) reaction by automated search for reaction pathways using the artificial force induced reaction (AFIR) method, for the simplest set of reactants, H 2 CO + C 2 H 4 . The search found all previously suggested pathways automatically without using any guess about the reaction mechanism. Even the reaction product was not assumed. In addition, a comprehensive view of the reaction path network obtained in the present extensive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Furthermore, one cannot be certain that all relevant MECIs have been found for polyatomic molecules. In order to address this problem, some efforts are being made to develop algorithms that can perform more automatic searches without intuition involved. In a recent study, MECIs are found using driving coordinates that can be generated using a combinatorial search and subsequent optimization . We are not going to discuss these approaches in detail here but rather discuss the traditional algorithms for locating MECIs starting from an initial guess.…”
Section: Conical Intersectionsmentioning
confidence: 99%
“…Furthermore, one cannot be certain that all relevant MECIs have been found for polyatomic molecules. In order to address this problem, some efforts are being made to develop algorithms that can perform more automatic searches without intuition involved. In a recent study, MECIs are found using driving coordinates that can be generated using a combinatorial search and subsequent optimization . We are not going to discuss these approaches in detail here but rather discuss the traditional algorithms for locating MECIs starting from an initial guess.…”
Section: Conical Intersectionsmentioning
confidence: 99%
“…Molecules decay to the lower electronic state in higher-energy regions of the CI hyperspace in the actual dynamics, and characterization of higher-energy CI regions have also been made [16][17][18]. Automated methods have also been developed for systematic exploration of MECI geometries [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The model function has local minima near MECIs, and approximate MECI geometries can therefore be obtained by exploring local minima on the model function. Three automated reaction path search methods, i.e., anharmonic downward distortion following (ADDF) [24][25][26], multi component artificial force induced reaction (MC-AFIR) [27], and single component (SC)-AFIR [28], have been employed to search for local minima on the model function [20][21][22]. Especially, the SMF/SC-AFIR approach has enabled automated search of MECI geometries in systems including more than 30 atoms routinely using a laboratory size computer cluster [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, preparing initial geometries for all accessible MECIs is not easy. Therefore, we have developed the seam model function (SMF) approach, which allowed for automated MECI searches using an automated local minimum search method. The SMF can be combined with any local minimum search method. In our previous studies, the anharmonic downward distortion following (ADDF) method and a version of the artificial force induced reaction ,, (AFIR) method called multicomponent AFIR (MC-AFIR) have been employed.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the ADDF is suited for searches of unimorecular isomerization and dissociation pathways, and the MC-AFIR, for bimolecular and multicomponent reactions. Therefore, the combined SMF/ADDF has been applied to studies of photodissociation mechanisms, and the SMF/MC-AFIR, to a photoaddition reaction …”
Section: Introductionmentioning
confidence: 99%